Taking the lead for campus-community-partnerships in Austria - Fahrenwald, Claudia; Resch, Katharina; Rameder, Paul; Fellner, Magdalena; Slepcevic-Zach, Peter; Knapp, Mariella (Frontiers in Education, 2023)
Higher education institutions (HEIs) have been going through far-reaching processes of transformation in terms of their missions in teaching, research, and societal impact. Contrary to their previous understanding and mission, Austrian universities are now increasingly required to contribute evidence from research and teaching to meet social challenges and to cooperate with community partners. This forces an understanding of HEIs as a driver for social innovation and requires educational leadership on multiple levels. Overall, campus community partnerships (CCPs) emerge as a dimension of a new culture of cooperation between HEIs and civil society which includes individual, organizational and inter-organizational learning. As, CCPs basically depend on the individual efforts, ambitions and networks of faculty members and educators we raise the questions, (1) who takes the lead for their initiation and maintenance, and (2) to which degree these partnerships have been institutionalized and supported so far. These questions are discussed in the framework of their significance for educational leadership for the establishment of suitable framework conditions for the promotion of social innovation for CCPs. These questions are particularly of interest for the German speaking countries like Austria, since CCPs in this context still have little tradition across the higher education sector. In this brief research report, results from a recent survey (2022; N = 107) concerning the initiation, support structures and formalization of CCPs in Austrian HEIs are presented, and conclusions for educational leadership principles for CCPs are discussed.